Soil Quality Assessment of Sesame-Growing Soils with Different Productivity in the Northern Telangana Zone, India - M. Deepthi; R. Sai Kumar; P. Ravi; O. Sampath (Archives of Current Research International, 2024)
Present study was carried out in major sesame growing areas of Northern Telangana zone in districts namely; Nizamabad, Jagtial, Nirmal and Kamareddy. The main objective of this study is to assess the soil quality and to find out the relation between sesame yield and soil quality index. Based on the seed yield data of sesame, the above-mentioned districts were divided into high, medium and low productivity zones. 50 samples from each productivity zone with a total of 150 surface soil samples (0-15 cm were collected and analysed for various physical, physico-chemical, chemical and biological properties. Physical properties included texture, bulk density and water holding capacity. Physico-chemical properties like pH, EC and organic carbon were analysed. Chemical properties of soil namely available nitrogen, available phosphorus, available potassium, available sulphur, exchangeable bases like exchangeable calcium and magnesium, potassium and sodium, available micronutrients like iron, copper, manganese and zinc were analysed. Biological properties like urease, acid and alkaline phosphatase and labile carbon were analysed. Principal component analysis, minimum dataset was derived which contained available nitrogen, sand, pH, available phosphorus, exchangeable calcium and magnesium and urease with 70.81% variance. These are identified as the key indicators of soil quality. Mean soil quality index values were 0.669, 0.549 and 0.443 for high, medium and low sesame productivity zones respectively and is in the order of high>medium>low sesame productivity zones. Percent contribution of MDS to SQI are in the order of, available nitrogen (44.44%> pH (16.85% >exchangeable calcium (9.87%> exchangeable magnesium (8.89%> urease (7.86%> available phosphorus (7.38% > sand (4.89%. This study concluded that the SQI was more significantly positively correlated with sesame yield, which revealed that soil variables from the minimum data set had biological significance and effectively evaluated the status of the sesame growing soils of Northern Telangana Zone.